FORENSIC ACCOUNTING AND FINANCIAL PERFORMANCE OF TERTIARY INSTITUTIONS IN PORT HARCOURT, RIVERS STATE - Akinyemi, Babajide Oloyode; Eke, Haniel Okorafor (Ph.D) (American Journals, 2023)
The issue of fraud has become an omen that is wide spreading in almost all the institutions of the nation; curtailing this ugly menace has proven abortive, it rather keeps growing even among the younger generation of today. Primarily, the paper aims to investigate the nexus between forensic accounting and its tools on financial performance of tertiary institutions in Port Harcourt, Rivers State; its objectives specifically look to: examine the association between forensic auditing and financial performance of tertiary institutions in Port Harcourt, Rivers State and to determine the affiliation between data mining and financial performance of tertiary institutions in Port Harcourt, Rivers State. Fraud preventive theory was used as the underpinning for the paper. The population of the study comprised of the three main universities Port Harcourt aspect of Rivers State in Nigeria; thus, they University of Port Harcourt, Rivers State University and Ignatius Ajuru University of Education and sample determined using a judgmental sampling of the non-probability sampling method. Product moment correlation coefficient was used for the analysis, and it was done under the help of Statistical Package for Social Sciences (SPSS) version 23. The findings revealed that forensic auditing has a solid substantial connection and affirmatively correlates with financial performance at a r = 0.904 and a Pv = 0.000, and that data mining has a weak insubstantialconnection and adversely correlates with financial performance at a r = -0.212 and a Pv = 0.964. The authors recommended that management of tertiary institutions should emphasize and enhance use of forensic measures as this will enable them improve on net profit margin. They also recommended that the management should ensure that the institution adapts to new technological changes taking place in the world to ensure that they have a well-structured system to accommodate these changes.
Keywords: Data Mining, Forensic Auditing, Forensic Accounting, Financial Performance